Solid-state lithium-sulfur battery

CN122930822APending Publication Date: 2026-10-16TOYOTA JIDOSHA KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610363055.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-08
Filing Date
2026-03-24
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

[0018] The solid-state lithium-sulfur battery, particularly the solid-state lithium metal-sulfur battery, according to the present invention can still have relatively good cycle characteristics despite using sulfur-based positive electrode active materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930822A_ABST
    Figure CN122930822A_ABST
Patent Text Reader

Abstract

Provided is a solid-state lithium-sulfur battery, which is a solid-state lithium-sulfur battery having, in order, a positive electrode current collector layer, a positive electrode active material layer, a solid electrolyte layer, and a negative electrode current collector layer, wherein the positive electrode active material layer has a sulfur-based active material, a solid electrolyte, and a resin binder that binds them to each other, the resin binder is a butadiene rubber that does not contain fluorine, and the content rate of the resin binder in the positive electrode active material layer is more than 0.0 mass% and 0.5 mass% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to solid-state lithium-sulfur batteries, particularly solid-state lithium metal-sulfur batteries. Background Technology

[0002] Solid-state lithium-sulfur batteries are secondary batteries that use a solid electrolyte as the electrolyte and a sulfide-based active material as the positive electrode active material. Compared to liquid batteries that use only a liquid electrolyte, solid-state lithium-sulfur batteries offer higher charging performance due to the use of a solid electrolyte, and also achieve high energy density by using a sulfide-based active material as the positive electrode active material.

[0003] Solid-state lithium metal-sulfur batteries are secondary batteries that use a solid electrolyte as the electrolyte, a sulfur-based active material as the positive electrode active material, and a lithium metal deposition and dissolution reaction occurs at the negative electrode during charging and discharging. In addition to the advantages of solid-state lithium-sulfur batteries, these batteries also exhibit high energy density due to the lithium metal deposition and dissolution reaction at the negative electrode during charging and discharging.

[0004] Regarding such solid-state lithium-sulfur batteries, Japanese Patent Application Laid-Open No. 2020-119761 discloses a method for manufacturing a positive electrode for an all-solid-state lithium-sulfur battery. The method includes a step of coating a positive electrode slurry containing a positive electrode active material, a solid electrolyte, a binder, and a solvent onto a positive electrode current collector to form a positive electrode active material layer. The positive electrode active material contains sulfur, and the number of solvent donors is 19 or less. Summary of the Invention

[0005] Solid-state lithium-sulfur batteries, especially solid-state lithium metal-sulfur batteries, exhibit significant expansion and contraction of the positive electrode active material layer during charging and discharging compared to other lithium-ion batteries that do not use sulfur-based positive electrode active materials, resulting in relatively poor cycle characteristics.

[0006] Therefore, the purpose of this invention is to improve the cycle characteristics of solid-state lithium-sulfur batteries, especially solid-state lithium metal-sulfur batteries.

[0007] The present invention achieves the above objectives through the following means.

[0008] <Method 1>

[0009] A solid-state lithium-sulfur battery, comprising, sequentially a positive electrode current collector layer, a positive electrode active material layer, a solid electrolyte layer, and a negative electrode current collector layer, wherein... The positive electrode active material layer comprises a sulfur-based active material, a solid electrolyte, and a resin binder that binds them together. The resin binder is fluorine-free butadiene rubber, and The content of the resin binder in the positive electrode active material layer is greater than 0.0% by mass and less than 0.5% by mass.

[0010] <Method 2>

[0011] According to the solid-state lithium-sulfur battery of method 1, the resin binder is hydrogenated butadiene rubber, styrene-butadiene rubber, or combinations thereof with amine groups introduced into it.

[0012] <Method 3>

[0013] According to the solid-state lithium-sulfur battery of method 1, the resin binder is styrene-butadiene rubber.

[0014] <Method 4>

[0015] According to any one of methods 1 to 3, in a solid lithium-sulfur battery, at least a portion of the solid electrolyte is self-formed during the first charge of the solid lithium-sulfur battery.

[0016] <Method 5>

[0017] The solid-state lithium-sulfur battery according to any one of methods 1 to 4, in the charging state, sequentially comprises the positive electrode current collector layer, the positive electrode active material layer, the solid electrolyte layer, the lithium metal layer and the negative electrode current collector layer.

[0018] The solid-state lithium-sulfur battery, particularly the solid-state lithium metal-sulfur battery, according to the present invention can still have relatively good cycle characteristics despite using sulfur-based positive electrode active materials. Attached Figure Description

[0019] The features, advantages, and technical and industrial significance of exemplary embodiments of the present invention will now be described with reference to the accompanying drawings, in which the same reference numerals denote the same elements.

[0020] Figure 1 This is a schematic diagram illustrating the solid-state lithium-sulfur battery of the present invention. Detailed Implementation

[0021] The embodiments of the present invention will now be described in detail. It should be noted that the present invention is not limited to the following embodiments, and various modifications can be made within the scope of the present invention.

[0022] Solid-state lithium-sulfur batteries

[0023] The solid-state lithium-sulfur battery of the present invention comprises, in sequence, a positive electrode current collector layer, a positive electrode active material layer, a solid electrolyte layer, and a negative electrode current collector layer. Furthermore, in this solid-state lithium-sulfur battery of the present invention, the positive electrode active material layer comprises a sulfur-based active material, a solid electrolyte, and a resin binder binding them together. The resin binder is a fluorine-free butadiene rubber, and the content of the resin binder in the positive electrode active material layer is greater than 0% by mass and less than 0.5% by mass.

[0024] Solid-state lithium-sulfur batteries, particularly solid-state lithium metal-sulfur batteries, according to the present invention, can still exhibit relatively good cycle characteristics despite using sulfur-based positive electrode active materials.

[0025] While not limited by theory, it can be assumed that by containing only a small amount of fluorine-free butadiene rubber as a resin binder in the positive electrode active material layer, the binder easily deforms along with the expansion and contraction of the positive electrode active material layer during the charging and discharging of the solid-state lithium-sulfur battery, thus providing relatively good cycle characteristics. Conversely, it can be assumed that when the content of this resin binder is relatively high, the binder forms a relatively large block, which is difficult to deform with expansion and contraction, and therefore the binder is easily peeled off from the sulfur-based active material and the solid electrolyte.

[0026] Specifically, for example Figure 1 As shown, the solid-state lithium-sulfur battery 100 of the present invention sequentially comprises a positive electrode current collector layer 140, a positive electrode active material layer 110, a solid electrolyte layer 120, and a negative electrode current collector layer 150. In particular, when the solid-state lithium-sulfur battery of the present invention is a solid-state lithium metal-sulfur battery, i.e., a solid-state lithium-sulfur battery in which lithium metal deposition and dissolution reactions occur at the negative electrode during charging and discharging, the solid-state lithium metal-sulfur battery 100 of the present invention, in the charging state, sequentially comprises a positive electrode current collector layer 140, a positive electrode active material layer 110, a solid electrolyte layer 120, a lithium metal layer 130, and a negative electrode current collector layer 150.

[0027] The positive electrode active material layer 110 has a sulfur-based active material 111, a solid electrolyte (not shown), and a resin binder 112 that binds them together.

[0028] The solid electrolyte layer 120 may have a solid electrolyte 121 and a resin adhesive 122 for bonding the solid electrolytes 121 together.

[0029] The lithium metal layer 130 contains lithium metal. During the discharge of the solid-state battery 100, the lithium metal in the lithium metal layer 130 is ionized into lithium ions, which are then inserted into the positive electrode active material layer 110 via the solid electrolyte layer 120. During the charging of the solid-state battery 100, the lithium ions are deintercalated from the positive electrode active material layer 110, and lithium metal is deposited between the solid electrolyte layer 120 and the negative electrode current collector layer 150 to form the lithium metal layer 130.

[0030] It should be noted that, in this invention, a "solid-state battery" refers to a battery that uses at least a solid electrolyte as the electrolyte. Therefore, a solid-state battery can use a combination of solid and liquid electrolytes as the electrolyte. Additionally, in this invention, a "solid-state battery" can also be an all-solid-state battery, that is, a battery that uses only a solid electrolyte as the electrolyte.

[0031] <Positive current collector layer>

[0032] The shape of the positive current collector layer is not particularly limited; for example, it can be foil or plate-shaped. The positive current collector layer can consist of two or more foils or layers. The positive current collector layer can have a metal foil or a layer composed of a resin composition containing resin and conductive additives.

[0033] The metal constituting the metal foil may be selected from at least one of Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, V, Mg, Pb, Ge, In, Sn, Zr, and stainless steel. Particularly from the viewpoint of ensuring oxidation resistance, Al is preferred. The positive current collector layer may be a layer formed by depositing or vapor-depositing the aforementioned metal onto the metal foil or substrate.

[0034] There is no particular limitation on the thickness of the positive electrode current collector layer; it can be greater than 0.1μm or greater than 1μm, or less than 1mm or less than 100μm.

[0035] <Positive Electrode Active Material Layer>

[0036] The positive electrode active material layer contains sulfur-based active materials, a solid electrolyte, and a resin binder that binds them together. The positive electrode active material layer may further contain other active materials, conductive additives, etc.

[0037] The shape of the positive electrode active material layer is not particularly limited; for example, it can be a sheet with a generally planar shape. The thickness of the positive electrode active material layer is not particularly limited; for example, it can be 0.1 μm or more, 1 μm or more, or 10 μm or more, or it can be less than 2 mm, less than 1 mm, or less than 500 μm.

[0038] (Sulfur-based reactive substances)

[0039] Regarding the sulfur-based active material contained in the positive electrode active material layer, it is sufficient as long as it can react with lithium ions, which serve as charge compensation ions, during discharge to generate compounds containing sulfur and lithium (such as sulfides like Li2S) as discharge products, and can release lithium ions during charging.

[0040] Sulfur-based reactive substances can contain elemental sulfur or be composed of elemental sulfur. Elemental sulfur can be cyclooctasulfide (S8) or other substances. Cyclooctasulfide (S8) can be α-sulfur, β-sulfur, γ-sulfur, or a combination thereof.

[0041] Sulfur-based active substances can be dissolved in solid electrolytes or chemically bonded to solid electrolytes. For example, when the solid electrolyte is a phosphorus-containing sulfide such as phosphorus pentasulfide (P2S5), the sulfur in the sulfur-based active substance can be chemically bonded to the sulfur in the phosphorus-containing sulfide.

[0042] The shape of the sulfide-based active material is not particularly limited; for example, it can be particulate. The particle size of the sulfide-based active material can be, for example, greater than 1 nm, greater than 5 nm, or greater than 10 nm, and can be less than 500 μm, less than 100 μm, less than 50 μm, or less than 30 μm. It should be noted that the particle size of the positive electrode active material is the particle size (median diameter) at the 50% cumulative value of the volume-based particle size distribution obtained by laser diffraction / scattering method.

[0043] Whether the positive electrode active material layer contains sulfur-based active materials can be determined by various analyses such as XAFS, XRD, and NMR on the composite material constituting the positive electrode active material layer. For example, when the positive electrode active material layer is composed of a composite material containing elemental sulfur, when the X-ray diffraction pattern of the composite material is obtained using CuKα as the X-ray source, diffraction peaks originating from elemental sulfur will be identified in the X-ray diffraction pattern. Diffraction peaks originating from elemental sulfur typically appear at 2θ = 23.05°±0.50°, 25.84°±0.50°, and 27.70°±0.50°.

[0044] The content of sulfur-based active materials in the positive electrode active material layer can be appropriately determined according to the target battery performance. For example, relative to the positive electrode active material layer, the content of sulfur-based active materials can be more than 10% by mass, more than 20%, more than 30%, more than 40% by mass, more than 50% by mass, or more than 60% by mass, or it can be less than 100% by mass or less than 90% by mass.

[0045] (Solid electrolyte)

[0046] Solid electrolytes can be inorganic solid electrolytes or organic polymer electrolytes. In particular, inorganic solid electrolytes exhibit excellent ionic conductivity and heat resistance. Examples of inorganic solid electrolytes include oxide solid electrolytes, sulfide solid electrolytes, and ionically bonded inorganic solid electrolytes. Among inorganic solid electrolytes, sulfide solid electrolytes, especially those containing at least Li, S, and P as constituent elements, exhibit superior performance. Alternatively, among inorganic solid electrolytes, ionically bonded solid electrolytes, especially those containing at least Li, Y, and a halogen (at least one of Cl, Br, I, and F) as constituent elements, exhibit superior performance. Solid electrolytes can be amorphous or crystalline.

[0047] The particle size of the solid electrolyte can be less than 1.0 μm, less than 0.9 μm, less than 0.8 μm, less than 0.7 μm, or less than 0.5 μm, or greater than 0.1 μm, 0.2 μm, or 0.3 μm. The particle size of the solid electrolyte is the particle size (median diameter) at the 50% cumulative value in the volume-based particle size distribution obtained by laser diffraction / scattering method.

[0048] The oxide solid electrolyte can be selected from lithium lanthanum zirconate, LiPON, Li 1+X Al X Ge 2-X One or more of the following: (PO4)3, Li-SiO glass, and Li-Al-SO glass. Furthermore, when oxide solid electrolytes are combined with liquid electrolytes, ionic conductivity can be improved.

[0049] Sulfide solid electrolytes may contain, for example, Li, X (where X is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In), and S. Furthermore, sulfide solid electrolytes may further contain at least one of O and a halogen. Additionally, sulfide solid electrolytes may contain S as the main component of the anionic element.

[0050] Sulfide solid electrolytes can be selected from, for example, Li₂S-P₂S₅, Li₂S-P₂S₅-LiI, Li₂S-P₂S₅-GeS₂, Li₂S-P₂S₅-Li₂O, Li₂S-P₂S₅-Li₂O-LiI, Li₂S-P₂S₅-LiI, Li₂S-SiS₂, Li₂S-SiS₂-LiI, Li₂S-SiS₂-LiBr, Li₂S-SiS₂, Li₂S-SiS₂-LiI, Li₂S-SiS₂-LiBr, Li₂S-SiS₂-LiCl, Li₂S-SiS₂-B₂S₃-LiI, Li₂S-SiS₂-P₂S₅-LiI, Li₂S-B₂S₃, Li₂S-P₂S₅-ZmSn (where m and n are positive numbers, and Z is any one of Ge, Zn, and Ga), Li₂S-GeS₂, Li₂S-SiS₂-Li₃PO₄, Li₂S-SiS₂-Li x MO y (Where x and y are positive numbers, and M is any one of P, Si, Ge, B, Al, Ga, and In.)

[0051] In the solid-state lithium-sulfur battery of the present invention, at least a portion of the solid electrolyte can be self-formed during the first charge of the solid-state lithium-sulfur battery. That is, the solid-state lithium-sulfur battery of the present invention contains a phosphorus-containing sulfide, such as P2S5, before the first charge, which reacts at least partially with lithium during the first charge to form a sulfide solid electrolyte as described above. Such a self-formed solid electrolyte during the first charge provides a suitable ion conduction network and is therefore preferred.

[0052] In this phosphorus-containing sulfide, the constituent elements may include at least phosphorus and sulfur, and may further include other elements. Examples of other elements include one or more of Ge, Sn, Si, B, and Al. Furthermore, the constituent elements of the phosphorus-containing sulfide may include phosphorus, sulfur, and the aforementioned other elements; however, it may not contain lithium. P2S5 is an example of a phosphorus-containing sulfide. Additionally, the phosphorus-containing sulfide may have a positive phosphorus structure (PS4 structure). The shape of the phosphorus-containing sulfide is not particularly limited; for example, it may be particulate. Whether the positive electrode active material layer before the first charge contains phosphorus-containing sulfides can be determined by performing various analyses such as XAFS, XRD, and NMR on the positive electrode active material layer.

[0053] (Adhesive)

[0054] In the solid-state lithium-sulfur battery of the present invention, the resin binder is a fluorine-free butadiene rubber, particularly hydrogenated butadiene rubber with amine groups, styrene-butadiene rubber, and combinations thereof, especially styrene-butadiene rubber.

[0055] Hydrogenated butadiene rubber with introduced amino groups is obtained by introducing amino groups at the ends of hydrogenated butadiene rubber. Here, hydrogenated butadiene rubber is a resin obtained by hydrogenating some or all of the unsaturated bonds of butadiene rubber, and it exhibits high flexibility. Hydrogenated butadiene rubber with introduced amino groups has improved adhesion strength to solid electrolytes due to the introduction of amino groups as polar groups. Styrene-butadiene rubber can be hydrogenated or not.

[0056] The resin binder content in the positive electrode active material layer is greater than 0.0% by mass and less than 0.5% by mass. This content can be greater than 0.1% by mass or greater than 0.2% by mass, and can be less than 0.4% by mass.

[0057] (Active substances other than sulfur-based active substances)

[0058] Besides sulfide-based active materials, active materials can be various lithium-containing compounds. These lithium-containing compounds can be lithium cobalt oxide, lithium nickel oxide, Li... 1+α Ni 1 / 3 Co 1 / 3 Mn 1 / 3 O 2+δ Lithium manganese oxide, spinel-type lithium compounds (with Li) 1+x Mn 2-x-y M y O4 (where M is selected from one or more of Al, Mg, Co, Fe, Ni, and Zn) indicates the composition of heteroelemental substitutions such as Li-Mn spinel, lithium titanate, and lithium metal phosphate (LiMPO4, etc., where M is selected from one or more of Fe, Mn, Co, and Ni), as well as various lithium-containing oxides. It should be noted that the higher the proportion of sulfide active materials in the overall positive electrode active material, the easier it is for the positive electrode active material layer to expand and contract during charging and discharging.

[0059] (Conductive additive)

[0060] The conductive additive is not particularly limited and can be, for example, carbon. Carbon can be, for example, one or more of carbon nanotubes, vapor-grown carbon fibers (VGCF), acetylene black, furnace black, Ketjen black, activated carbon, and graphene. In particular, when the positive electrode active material layer contains carbon nanotubes, high performance is easily ensured as a battery. Other conductive additives include, for example, one or more conductive additives composed of various metallic materials. The conductive additive can be, for example, in particulate or fibrous form, and its size is not particularly limited.

[0061] (Manufacturing method of positive electrode active material layer)

[0062] The positive electrode active material layer can be manufactured using known methods. For example, the positive electrode active material layer can be formed by dry or wet molding of a positive electrode composite material containing the above-mentioned components. The positive electrode active material layer can be formed on the positive electrode current collector layer or formed separately from the positive electrode current collector layer.

[0063] <Solid Electrolyte Layer>

[0064] The solid electrolyte layer comprises a solid electrolyte and an optional resin binder. The resin binder used herein is not particularly limited, and may be, for example, one or more selected from butadiene rubber, butene rubber, acrylate butadiene rubber, styrene-butadiene rubber, polyvinylidene fluoride, polytetrafluoroethylene, polyimide, etc. Alternatively, the resin binder used herein may be the resin binder described for the positive electrode active material layer.

[0065] In the solid electrolyte layer, the content of resin binder can be 5% by mass or more and 15% by mass or less. When the solid electrolyte layer contains more resin binder, the flexibility of the solid electrolyte increases, but the battery performance decreases. The above-mentioned content can be 6% by mass or more, 7% by mass or more, 8% by mass or more, 9% by mass or more, or 10% by mass or more, or it can be less than 15% by mass, less than 14% by mass, less than 13% by mass, less than 12% by mass, or less than 11% by mass.

[0066] There is no particular limitation on the content of solid electrolyte, which can be appropriately determined according to the application and performance of the thin film for solid-state batteries. For example, relative to the solid electrolyte layer, the content of solid electrolyte can be more than 1% by mass, more than 5% by mass, more than 10% by mass, more than 15% by mass, or more than 20% by mass, or it can be less than 95% by mass, less than 90% by mass, less than 80% by mass, less than 70% by mass, less than 60% by mass, or less than 50% by mass.

[0067] The solid electrolyte layer can consist of one layer or two or more layers. For example, the solid electrolyte layer may have a first layer disposed on the positive electrode side and a second layer disposed on the negative electrode side. The first layer may contain a first solid electrolyte, and the second layer may contain a second solid electrolyte. The first solid electrolyte and the second solid electrolyte may be different types of each other. The first solid electrolyte and the second solid electrolyte may each be at least one selected from oxide solid electrolytes, sulfide solid electrolytes, and ion-bonded solid electrolytes, as described later. For example, the first layer may contain an ion-bonded solid electrolyte, and the second layer may contain at least one of ion-bonded solid electrolytes and sulfide solid electrolytes.

[0068] The shape of the solid electrolyte layer is not particularly limited; for example, it can be a sheet with a generally planar surface. The thickness of the solid electrolyte layer is not particularly limited; for example, it can be 0.1 μm or more, 1 μm or more, or 10 μm or more, or it can be less than 2 mm, less than 1 mm, or less than 500 μm.

[0069] (Manufacturing method of solid electrolyte layer)

[0070] The solid electrolyte layer can be formed, for example, by dry or wet molding of a solid electrolyte composite material containing the aforementioned solid electrolyte and resin binder.

[0071] <Lithium Metal Layer>

[0072] The lithium metal layer serves as the negative electrode active material layer. The lithium metal layer is composed of metallic lithium. "Metallic lithium" can be elemental lithium or a lithium alloy.

[0073] During charging, lithium ions moving from the positive electrode accept electrons and precipitate between the electrolyte layer and the negative electrode current collector layer as metallic lithium or in an alloy with other metals, forming a metallic lithium layer. Furthermore, during discharging, the lithium ions in the negative electrode layer are ionized and return to the positive electrode layer.

[0074] There is no particular limit to the amount of lithium metal deposited during charging; it can be appropriately determined based on the target battery performance. However, excessive lithium metal deposits may raise concerns about pressure concentration. The amount of lithium metal deposited can be such that it enables the battery's charging capacity to reach, for example, a level between 1 mAh / cm² and 5 mAh / cm².

[0075] The shape of the lithium metal layer is not particularly limited; for example, it can be a sheet with a generally planar surface. The thickness of the lithium metal layer is not particularly limited; for example, it can be 0.1 μm or more, 1 μm or more, or 10 μm or more, or it can be less than 2 mm, less than 1 mm, or less than 500 μm.

[0076] There are no particular limitations on lithium alloys. For example, lithium alloys can be Li-Mg, Li-Sn, Li-Al, Li-B, Li-C, Li-Si, Li-Ca, Li-Ga, Li-Ge, Li-As, Li-Se, Li-Ru, Li-Rh, Li-Pd, Li-Ag, Li-Au, Li-Cd, Li-In, Li-Sb, Li-Ir, Li-Pt, Li-Hg, Li-Pb, Li-Bi, Li-Zn, Li-Tl, Li-Te, Li-At, etc. A lithium alloy can be of only one type or two or more types.

[0077] <Negative current collector layer>

[0078] The negative electrode current collector layer can be a metal foil or a metal mesh, or it can be a carbon sheet. In particular, from an operational point of view, a metal foil is preferred. The negative electrode current collector layer can be composed of two or more metal foils or sheets, and when the negative electrode current collector layer is composed of two or more metal foils or sheets, there can be any layer between the two or more metal foils.

[0079] Examples of metals constituting the metal foil include Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, and stainless steel. In particular, from the viewpoint of ensuring resistance to reduction and preventing alloying with lithium, it is preferable to include at least one metal selected from Cu, Ni, and stainless steel, and more preferably, at least one metal selected from Ni and stainless steel.

[0080] The negative electrode current collector layer may have a coating on its surface. For example, the negative electrode current collector layer may have a protective layer on its surface. The protective layer may, for example, contain Mg. It is believed that by having a protective layer containing Mg, the diffusion of Li on the surface of the negative electrode current collector layer can be promoted, while increasing the affinity between metallic lithium and the negative electrode current collector layer, suppressing the voids between the negative electrode current collector layer and metallic lithium, and allowing metallic lithium to be deposited more uniformly on the surface of the negative electrode current collector layer.

[0081] There is no particular limitation on the thickness of the negative electrode current collector layer; it can be greater than 0.1μm or greater than 1μm, or less than 1mm or less than 100μm.

[0082] Manufacturing Method of Solid-State Lithium-Sulfur Batteries

[0083] The solid-state lithium-sulfur battery of the present invention can be manufactured by known methods. Specifically, for example, the method for manufacturing the solid-state battery of the present invention may include: S1: A positive electrode active material layer is formed on the positive electrode current collector layer; S2: Obtain a laminate having sequentially formed a positive current collector layer, a positive active material layer, a solid electrolyte layer, a lithium metal layer, and a negative current collector layer; and S3: The above-mentioned stacked body is housed in the outer casing.

[0084] In step S1, sulfur-based active materials constituting the positive electrode active material layer can be dispersed in a solvent to obtain a positive electrode composite material slurry. The positive electrode composite material slurry is then coated onto the positive electrode current collector layer using a doctor blade or similar tool, and subsequently dried to form the positive electrode active material layer on the positive electrode current collector layer. The solvent used in this step is not particularly limited, and various organic solvents can be used.

[0085] In step S2, the layers can be stacked with a solid electrolyte layer sandwiched between the lithium metal layer and the positive electrode active material layer to obtain a laminate containing a negative electrode current collector layer, a lithium metal layer, a solid electrolyte layer, a positive electrode active material layer, and a positive electrode current collector layer in sequence. Terminals or other components can be installed on the laminate as needed.

[0086] In step S3, the laminate is housed in a battery casing, and if a liquid electrolyte is required, an electrolyte is filled into the battery casing. The laminate is then sealed inside the battery casing to obtain a solid-state battery.

[0087] Example 1

[0088] The present invention has been specifically illustrated by means of examples and comparative examples, but the present invention is not limited thereto.

[0089] In the following embodiments and comparative examples, solid-state lithium metal-sulfur batteries having the following stacked structure were fabricated and evaluated: Roughened aluminum foil / Positive electrode active material layer / Sulfide solid electrolyte (0.5μm) / Li-10 wt% Mg alloy foil (100μm) / Roughened nickel foil Specifically, the solid-state lithium metal-sulfur batteries of the embodiments and comparative examples were fabricated as follows. Furthermore, details of the solid-state lithium metal-sulfur batteries of the embodiments and comparative examples are described in Table 1 below.

[0090] 1. Fabrication of the positive electrode active material layer

[0091] Sulfur (vacuum-dried at 80°C), used as the positive electrode active material, P2S5 (as a solid electrolyte precursor), Li3PS4 (as a solid electrolyte), and single-walled carbon nanotubes (vacuum-dried at 120°C) were mixed in a mortar at a weight ratio of 42:35:23. 1.7 g of this mixture and 80 g of Φ4 mm zirconium oxide balls were added to a ball mill jar, and the mixture was stirred at 400 rpm for a total of 36 hours using a planetary ball mill. After ball milling, the mixture was dry-graded using a 38 μm sieve to obtain the sulfur-based positive electrode active material.

[0092] When the resin binder is hydrogenated butadiene rubber (ABR) with introduced amine groups, heptane is used as a solvent, and when the resin binder is styrene-butadiene rubber (SBR), mesitylene is used. The cathode composite slurry is prepared in such a way that the mass ratio of sulfur cathode active material to various resin binders reaches 99.7:0.3, 99.4:0.6 or 99.1:0.9.

[0093] The obtained positive electrode composite material slurry was coated on roughened aluminum foil with a coating gap of 220 μm, then pre-dried at 50 °C and formally dried at 100 °C for 30 minutes to obtain the positive electrode composite material layer coated on the positive electrode current collector foil.

[0094] 2. Fabrication of the solid electrolyte layer

[0095] Heptane was used as the dispersion medium, and a solid electrolyte slurry was prepared with a mass ratio of solid electrolyte (particle size: 0.5 μm): resin binder of 90.9:9.1.

[0096] The obtained solid electrolyte slurry was coated onto the release film with a coating gap of 450 μm, then pre-dried at room temperature for about 3 hours, and then formally dried at 165 °C for 1 hour to obtain the solid electrolyte layer.

[0097] The obtained solid electrolyte layer was punched into two circular plates with a diameter of 14.5 mm. The coated surfaces were then overlapped and pressed at a pressure of 6 tons at room temperature. After pressing, the release film was peeled off to obtain a self-supporting sulfide solid electrolyte layer.

[0098] 3. Fabrication of laminated battery cells

[0099] The positive electrode layer prepared in "1. Preparation of the positive electrode active material layer" above is punched into a circular plate with a diameter of 11.28 mm, the Li-10 wt% Mg alloy foil is punched into a circular plate with a diameter of 13.0 mm, and the roughened nickel foil used as the negative electrode current collector is punched into a circular plate with a diameter of 14.5 mm.

[0100] The circular plate-shaped Li-Mg foil and the circular plate-shaped roughened nickel foil obtained above are stacked together and pressed together under a pressure of 0.1 tons to obtain a circular plate-shaped negative electrode layer. The circular plate-shaped solid electrolyte sheet prepared in "2. Fabrication of Solid Electrolyte Layer" above is placed between the circular plate-shaped positive electrode layer and the circular plate-shaped negative electrode layer. The aluminum foil serving as the positive electrode tab is bonded to the positive electrode current collector, and the nickel foil serving as the negative electrode tab is bonded to the negative electrode current collector. Then, the resulting solid lithium metal-sulfur battery is vacuum sealed in a laminate. The sealed battery cell is isostatically pressed at 300 MPa using a cold isostatic press (CIP) to fabricate a laminated battery cell.

[0101] 4. Electrochemical Measurement

[0102] Within the cutoff voltage range of 3.1V-1.2V, a constant current charge-discharge test was conducted at 60℃ using the following scheme with 1C = 5.84mA / cm².

[0103] • Current density: 0.584 mA / cm² (equivalent to 0.1C)

[0104] • Adjustment (Cycle 0): Discharge to 1.2V

[0105] • After adjustment (first cycle onwards): Charge to 3.1V, discharge to 1.2V

[0106] The evaluation results are shown in Table 1 below.

[0107]

[0108] As can be understood from Table 1 above, when the resin binder of the positive electrode active material layer is hydrogenated butadiene rubber (ABR) with introduced amine groups, the solid lithium-sulfur battery of Example 1 with a resin binder content of 0.3% by mass in the positive electrode active material layer has a better discharge capacity after 1 cycle and 10 cycles compared with the solid lithium-sulfur batteries of Comparative Examples 1 and 2 with a content of 0.6% by mass or 0.9% by mass.

[0109] Furthermore, as can be understood from Table 1 above, when the resin binder of the positive electrode active material layer is styrene-butadiene rubber (SBR), the solid lithium-sulfur battery of Example 2, which has a resin binder content of 0.3% by mass in the positive electrode active material layer, has a better discharge capacity after 1 cycle and 10 cycles compared with the solid lithium-sulfur batteries of Comparative Examples 3 and 4, which have a resin binder content of 0.6% by mass or 0.9% by mass.

[0110] Furthermore, as can be understood from Table 1 above, the solid-state lithium-sulfur battery of Example 2, in which the resin binder of the positive electrode active material layer is styrene-butadiene rubber (SBR) with a content of 0.3% by mass, has superior discharge capacity after 1 cycle and 10 cycles compared to the solid-state lithium-sulfur battery of Example 1, in which the resin binder of the positive electrode active material layer is hydrogenated butadiene rubber (ABR) with introduced amine groups with a content of 0.3% by mass.

[0111] Furthermore, as can be understood from Table 1 above, when the resin binder of the positive electrode active material layer is styrene-butadiene rubber (SBR) and its content is 0.3% by mass, the solid lithium-sulfur battery of Example 2, which has a self-formed lithium-ion conductive phase in the positive electrode active material layer, has a better discharge capacity after 1 cycle and 10 cycles compared with the solid lithium-sulfur battery of Example 3, which does not have such a self-formed lithium-ion conductive phase.

Claims

1. A solid-state lithium-sulfur battery, comprising, sequentially, a positive electrode current collector layer, a positive electrode active material layer, a solid electrolyte layer, and a negative electrode current collector layer, wherein, The positive electrode active material layer comprises a sulfur-based active material, a solid electrolyte, and a resin binder that binds them together. The resin binder is fluorine-free butadiene rubber, and The content of the resin binder in the positive electrode active material layer is greater than 0.0% by mass and less than 0.5% by mass.

2. The solid-state lithium-sulfur battery according to claim 1, wherein, The resin binder is hydrogenated butadiene rubber, styrene-butadiene rubber, or combinations thereof, incorporating amine groups.

3. The solid-state lithium-sulfur battery according to claim 1, wherein, The resin binder is styrene-butadiene rubber.

4. The solid-state lithium-sulfur battery according to any one of claims 1 to 3, wherein, At least a portion of the solid electrolyte is formed during the first charge of the solid lithium-sulfur battery.

5. The solid-state lithium-sulfur battery according to any one of claims 1 to 3, wherein in the charging state it sequentially comprises the positive electrode current collector layer, the positive electrode active material layer, the solid electrolyte layer, the lithium metal layer and the negative electrode current collector layer.

Citation Information

Patent Citations

  • Manufacturing method of positive electrode for all-solid-state lithium-sulfur battery

    JP2020119761A